Consumer Protection Against Gas Stove Repair Businesses - Muhammad Andriansyah; H.R. Adianto Mardijono (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2025)
Legal protection for consumers is a crucial element in the legal relationship between business actors and the public, particularly in high-risk service sectors such as gas stove repair services. In practice, many consumers still experience losses due to negligence by service providers, whether caused by inadequate technical handling or insufficient information regarding the condition of the stove after repairs. This study aims to identify and analyze the forms of legal protection available to consumers who suffer losses as a result of such negligence, as well as to determine the types of legal liability that may be imposed on gas stove repair service providers. Using a normative legal research method, this study applies both legislative and conceptual approaches. The legislative approach examines relevant laws and regulations concerning consumer protection, while the conceptual approach analyzes legal principles and expert doctrines related to liability. The findings indicate that consumer protection is provided in two forms: preventive protection, which ensures product and service safety in accordance with Indonesian National Standards (SNI), and repressive protection, which is implemented through enforcement mechanisms such as claims for compensation or dispute resolution through the Consumer Dispute Settlement Agency (BPSK) or the courts. Business actors who commit negligence in providing repair services can be held legally responsible based on the principles of negligence or strict liability. To strengthen consumer protection, the study recommends the establishment of derivative regulations concerning technician certification, standardized repair service procedures, and integrated supervision of safety compliance within the gas stove repair service industry.